Improper Life : Technology and Biopolitics from Heidegger to Agamben - Campbell, Timothy C. (Book collections on Project MUSE., 2011)
Has biopolitics actually become thanatopolitics, a field of study obsessed with death? Is there something about the nature of biopolitical thought today that makes it impossible to deploy affirmatively? If this is true, what can life-minded thinkers put forward as the merits of biopolitical reflection? These questions drive Improper Life, Timothy C. Campbell's dexterous inquiry-as-intervention. Campbell argues that a "crypto-thanatopolitics" can be teased out of Heidegger's critique of technology and that some of the leading scholars of biopolitics-including Michel Foucault, Giorgio Agamben, a